PEMANFAATAN MAGGOT DALAM PENGOLAHAN LIMBAH ORGANIK RUMAH TANGGA UNTUK MENEKAN VOLUME SAMPAH DAN PEMANFAATAN MANGGOT SEBAGAI PAKAN ALTERNATIF TERNAK DI DESA PAKUAN KECAMATAN NARMADA - Saputra, Doni; Jurnal Wicara; Albayani, Jihan Fairuz; Arisma, Regita Cahya; Dewi, Aprilia Sintia; Ayuni, Diana; Anwar, Nabila Hanifah; Pebrianti, Nana Rizky; Talaohu, Ismail Al fatah; Komalasari, Arfika; Shifa, Nur Ilahis; Ramdhani, Miftah (Universitas Mataram, 2025)
The Community Service Program (KKN) for Village Empowerment (PMD) at the University of Mataram is a form of student service through interdisciplinary activities aimed at developing village potential and addressing community issues. The KKN program for the July–August 2025 period was implemented in Pakuan Village, Narmada District, West Lombok Regency, with the theme Green Economy. Pakuan Village is known as a tourist destination with potential in nature, agriculture, and local SMEs, yet it faces serious challenges in managing organic waste. Household and agricultural waste that is not properly managed can lead to environmental pollution and health problems.As a solution, the KKN PMD team introduced maggot (Black Soldier Fly/BSF) cultivation as a method of organic waste bioconversion. This approach not only effectively reduces organic waste volume but also produces nutrient-rich larvae that can be used as alternative animal feed, thereby providing additional economic value for the community. The activities carried out included socialization, hands-on training in maggot cultivation, and post-training monitoring to evaluate program outcomes.The results indicated an increase in community knowledge and skills in managing organic waste through maggot cultivation. Training participants, consisting of village officials, livestock groups, PKK women’s association, youth organizations, and the general public, showed strong enthusiasm and potential to continue the practice sustainably. Thus, this program can serve as an initial step in establishing environmentally friendly waste management while supporting the development of a green economy in Pakuan Village.